Gaya Kepemimpinan Lurah Dalam Dinamika Dan Aktivitas Warga - Sudarmawan, Herro; Askafi, Eka (Universitas Islam Kadiri, 2025)
This research aims to analyze the leadership style of the village head (Lurah) in influencing the dynamics and activities of residents in Bandar Kidul Urban Village, Mojoroto District, Kediri City. A qualitative descriptive approach was employed, using in-depth interviews, observations, and documentation as data collection techniques. The informants included village officials, neighborhood leaders (RT/RW), youth organization leaders, and community figures. The findings reveal that the Lurah adopts a participatory and communicative leadership style that encourages active citizen involvement in development programs and community activities. The Lurah has successfully fostered synergy among residents, enhanced community cohesion, and effectively facilitated public aspirations. These findings indicate that an adaptive and inclusive leadership style is a key factor in building harmonious social relations and improving the quality of community life.